Consanguineous unions and endogamy in families of beta-thalassaemia patients from two Mediterranean populations: Tunisia and Italy. (17th November 2019) - Weslati, Ramla; Ouederni, Monia; Ruffo, Giovanbattista; Khaled, Monia Ben; Kouki, Ridha; Di Girgenti, Caterine; Borsellino, Zelia; Sammartano, Irene; El Gazzah, Mohamed; El- Bok, Safia; Bejaoui, Mohamed
Abstract: Background: Consanguinity increases the incidence of recessive diseases such as beta-thalassaemia major (βTM), one of the most prevalent lethal inherited diseases in the world. Aim: This study aims to identify the frequency of endogamy and consanguinity in two Mediterranean βTM populations and to study the implication of socio-economic factors. Subjects and methods: A trans-sectional study was conducted in 203 Tunisian families and 75 Italian families. Data were collected using a questionnaire completed by patients and parents. Results: Complete endogamy and consanguinity were observed in 82.75% and 62.56% of Tunisian families, respectively. Complete endogamy was found in 90.67% of Italian families, no consanguinity was noted. The low occupation status of Tunisian mothers was associated with an increasing frequency of consanguinity ( p  = .01) and endogamy ( p  = .0003). Consanguinity was associated with low education level ( p  = .012) and low occupation status ( p =.047) of fathers. No significant association was found between endogamy and socio-economic factors in the Italian sample. Conclusions: High consanguinity and endogamy rates in Tunisian families may explain the frequency of βTM in Tunisia. The high endogamy rate in Italian families could also increase the frequency of βTM. Identification of geographical distribution and socio-economic factors leading to endogamy and consanguinity in these populations might help to improve βTM prevention.